Perbedaan Efektifitas Terapi Rebusan Daun Kelor dan Jus Apel terhadap Penurunan Kadar Gula Darah pada Penderita DM Tipe 2 - Risnawati Risnawati; Jenny Qilfianti Demmalewa (Jurnal Kesehatan Manarang, 2022)
The WHO in 2018 in the world has recorded that there are 422 million people suffering from diabetes mellitus or an increase of 8.5% of the adult population and also according to estimates there are deaths before the age of 70 years with a total of about 2.2 million. especially in countries with low and middle economic status. It is estimated that this will continue to grow until the year 2035, the number will reach around 600 million people. Controlling blood sugar levels with non-pharmacological therapy is generally safer. Lowering blood sugar levels can be done with non-formacological efforts in the form of consuming boiled Moringa leaves and apple juice by people with type II diabetes mellitus. Flavonoid compounds in the form of terpenoids contained in Moringa leaves are so effective and safe for lowering blood sugar. Apples contain large amounts of fiber. The entry of glucose into the bloodstream through the digestion of carbohydrates can be slowed by soluble fiber. To control glucose in people with diabetes mellitus this is very useful. It takes 120 – 180 minutes to process the fiber in apples so that it can lower glucose levels at that time. The purpose of this study was to examine the differences in the effectiveness of Moringa leaf decoction with apple juice in patients with type II diabetes mellitus on their blood sugar levels. The nature of this research is quantitative, using pre experimental design method through one group pre-test post-test design. The results of the paired t-test on respondents who were given Moringa leaf boiled water showed a p value = 0.001 which means that the correlation of blood sugar levels in the administration of Moringa leaf stew both before and after there was a significant difference in patients with type II DM and the results of the paired t-test the respondents who were given apple juice showed a p value = 0.116 which means the correlation of blood sugar levels in the administration of apple juice both before and after in patients with type II DM there was no significant difference. The conclusion of this study showed that boiled water of Moringa leaves was more effective in lowering blood sugar levels in type II DM patients.